Afinal, quem forma o formador? A formação continuada da coordenadora pedagógica de creche na rede municipal de São Bernardo do Campo - Ruiz, Cintia Berto Oliva (2023)
The purpose of this study is the continuing education of pedagogical coordinators in day care centers in the city of São Bernardo do Campo, in São Paulo. It is based on bibliographic sources and on field research with semi-structured interviews with six coordinators of the referred network. The objective is to understand how professionals understand the concept of continuing education, if this process seems important to them and to investigate whether they participate on their own initiative, by imposition of the Department of Education or for some other reason. The reduction of training received by the network, the discrepancy between some that are offered and the training needs of the coordinators constitute the identified problem: After all, who trains the trainer? It starts from the hypothesis that, for the coordinators, receiving continuing education is a prerequisite for the qualification of their work, but there is no clarity on how it should occur and, even, on their understanding of this concept. The theoretical references are based on a critical approach, considering that the individual is inserted in a context of multiple relationships. The educational contributions of Vera Placco and Edgar Morin dialogue with the theme of the need for change in the qualification of professionals, which must be dialogical. The result points to the need to reinforce the continuing education of nursery school coordinators, as well as the self-training of these professionals and the deepening of the training of pedagogical advisors, responsible for training network coordinators.